2016
DOI: 10.1016/j.fertnstert.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Grade and looseness of the inner cell mass may lead to the development of monochorionic diamniotic twins

Abstract: The occurrence of M-D twinning may be avoided by excluding blastocysts that contain decompacting ICMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…These results indicate that α-KG is an important metabolite that promotes embryonic development because α-KG reduces embryo ATP production and activates the TET enzyme, thereby enhancing the ICM and the competence of the blastocyst. The findings were consistent with previous observations that the ICM grade is positively related to birth weight (Licciardi et al 2015) and the survival rate of transplanted embryos (Otsuki et al 2016, Subira et al 2016). In humans, blastocysts with larger ICMs are more likely to implant after transfer than those with smaller ICMs (Richter et al 2001).…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that α-KG is an important metabolite that promotes embryonic development because α-KG reduces embryo ATP production and activates the TET enzyme, thereby enhancing the ICM and the competence of the blastocyst. The findings were consistent with previous observations that the ICM grade is positively related to birth weight (Licciardi et al 2015) and the survival rate of transplanted embryos (Otsuki et al 2016, Subira et al 2016). In humans, blastocysts with larger ICMs are more likely to implant after transfer than those with smaller ICMs (Richter et al 2001).…”
Section: Discussionsupporting
confidence: 92%
“…This sometimes occurs during frozen‐thawed embryo transfer cycles with hormone therapy and such conceptions cannot be eliminated in this study, although the incidence is very small 10, 16. Also, the analysis of the pronuclear size is restricted to 2‐D measurements in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This sometimes occurs during frozen-thawed embryo transfer cycles with hormone therapy and such conceptions cannot be eliminated in this study, although the incidence is very small. 10,16 Also, the analysis of the pronuclear size is restricted to 2-D measurements in this study. It is possible that more precise data could be obtained In this study, the authors focused on successful live birth rates, rather than blastocyst development and pregnancy rates, as >50% of blastocysts are known to have abnormal chromosomal configurations and most of those embryos result in a miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has indicated that the ICM grade or cell-adhesion looseness is related to MZT development [13], and in mouse, a delay in inter-cell adhesion has been shown to increase ICM division [14]. Because the scattered ICM arising from “8”-shaped hatching is considered to represent a state of cell-adhesion looseness, the occurrence of “8”-shaped hatching near the ICM could potentially be the factor that elicits MZT.…”
Section: Discussionmentioning
confidence: 99%